Graphitic Shells: Atomic Scale Evolution of Graphitic Shells Growth via Pyrolysis of Cobalt Phthalocyanine (Adv. Mater. Interfaces 23/2020). Issue 23 (3rd December 2020) - Zhang, Xiaofang; Yang, Feng; Tian, Dongliang; Zhao, Haofei; Wang, Rongming; Lau, Woon‐Ming
Abstract : By heating cobalt phthalocyanine (CoPc), bearing the dual roles of supplying carbon atoms and metamorphosizing a graphitization‐catalyst, the time‐evolution of CoPc to an intriguing Co‐Co3 C nano‐core enveloped by several graphitic layers are tracked, and out‐diffusion of carbon atoms from the core to fuel the growth of new outermost shell‐layers. More details can be found in article number 2001112 by Rongming Wang, Woon‐Ming Lau, and co‐workers.